PROGRAM BINA CINTA TUHAN (BCT) DALAM MEMBENTUK KARAKTER SISWA DI SEKOLAH SMP YPPSB SANGATTA UTARA - Nafsiyah, Faizatun; Afandi, Nur Kholik (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
The purpose of this research is to find out how the Bina Cinta Tuhan (BCT) Program at YPPSB Sangatta Utara Junior High School is used to develop student character. With this type of field research, which uses qualitative methodology, data was collected through documentation, interviews, and observations. There are three main conclusions that emerge from this research. Firstly, the BCT Program is implemented at YPPSB Junior High School through various religious activities incorporated into the curriculum, including collective prayers, spiritual values education, and faith festivals. Secondly, the curriculum effectively promotes the development of values such as honesty, responsibility, integrity and compassion. Third, the effects of this program are evident in the development of students' personalities that are more focused, empathetic, tolerant, devoted, and disciplined.